2015
DOI: 10.1111/rda.12587
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography of the Prostate Gland in Healthy Intact Dogs and Dogs with Benign Prostatic Hyperplasia

Abstract: To date, there is only scarce data on the evaluation of the prostate gland in dogs using computed tomography (CT). The aims of our study were to describe CT features of BPH in dogs and to determine the size of the prostate gland in healthy male dogs and dogs with benign prostatic hyperplasia (BPH) through CT. Additionally, we aimed to compare and establish the most useful parameters for CT measurements of the prostate in patients with BPH. The study population consisted of 20 healthy intact male dogs and 20 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 19 publications
1
33
2
Order By: Relevance
“…Schwarz et al described the prostate tissue of a benign hyperplasia (BPH) in the CT as a heterogeneous parenchyma compared to the healthy gland [28]. Similar findings were described by Pasikowska et al [18] who found that 75% of the patients with BPH had an inhomogeneous prostate and a mean age of 9 years. Additionally, cysts were often associated with the BPH [29].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Schwarz et al described the prostate tissue of a benign hyperplasia (BPH) in the CT as a heterogeneous parenchyma compared to the healthy gland [28]. Similar findings were described by Pasikowska et al [18] who found that 75% of the patients with BPH had an inhomogeneous prostate and a mean age of 9 years. Additionally, cysts were often associated with the BPH [29].…”
Section: Discussionmentioning
confidence: 61%
“…Lee et al [15] and Pasikowska et al [18] used CT for evaluating the canine prostate gland. Both research groups came to the conclusion that CT is a beneficial tool for evaluating the morphology of the prostate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, it is necessary to consider what others suggest in the sense that benign prostatic hyperplasia is heterogeneous in terms of tissue morphometry and expression of single important genes. This finding limits the use of a single biopsy based markers to predict biological behavior, and has significant impact on the ability of distinguishing longitudinal changes in tissue composition from sampling artifacts [51].…”
Section: Discussionmentioning
confidence: 99%